ANALISIS TINGKAT KEBISINGAN DAN POLA SEBARAN KEBISINGAN DI AREA PEMUKIMAN PENDUDUK DI SEKITA PASAR PAGI ARENGKA - Fitrya, Neneng; Febriani, Noni; Fahana, Rahmi (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
Settlement is located in the Village of East Sidomulyo RT 01 RW 02 and it is the closest settlement and directly exposed to the morning market of Arengka Pekanbaru activity. This market is potentialed to create of noise. The analysis of noise level is commited by collecting the data on seven points and commited for 4 days. Measure the noise level is using application of meter noise which downloaded on Smarthphone Samsung i8262 Galaxy Core Duos. the point that near with noise source market has higher noise intensity value than the points that are far away from the noise source market. The level of noise that consist in one of area that reached 64.455 dBA, this value has exceeded the threshold value (NAV) Kep - 51 / MEN / 1992 and SNI No. 16-7063-2004.